Formulation of Fish Feed Using Medicinal Herb Curcuma Amada and Its Biochemical and Haematological Changes in Labeo Rohita - Mallik, Ahmed Reyaz; Shammi, Qaiser Jehan; Telang, Sanjay (Journal of Drug Delivery and Therapeutics, 2019)
A characteristic feature of fish is the wide physiological range of blood parameters and also the large individual variations. The aim of this study was to evaluate the haematological profile and biochemical profile of fish Labeo rohita. The blood parameters viz., total WBC and RBC count, Hb, MCV, MCH and MCHC values were analyzed using standard methods. The differences found in this study can be attributed to the feeding behaviour, life style and adaptation of the different fish species to the habitat in which they dwell. Curcuma amada Roxb is commonly known as mango ginger. It is a perennial, rhizomatous, aromatic herb belonging to the family Zingiberaceae. The ranges of serum biochemistry vary from species to species and can be influenced by many biotic and abiotic factors such as water temperature, seasonal pattern, food, age and sex of the fish. The present study deals with the use of medicinal plant Curcuma amada in fish diet to study the biochemical and haematological profile on Labeo rohita a common fish. The plant was extracted and processed for decoction method. The extract obtained was then mixed with 0.5 kg salt (NaCl) and 1.0 kg fish feed powder in the ratio 10:1. Based on the results it is appropriate to conclude that the plant extract of Curcuma amada incorporated in fish diet may improve the biochemical and haematological profile in blood of fish Labeo rohita. It was observed that the herbal diet fed fishes exhibited significant increase in RBC, WBC, serum protein and globulin and also maintained hepatics disorder enzymes (ALT, AST, ALP) which may be considered as a sign of improvement in health status. It may be due to the presence active components i.e. carbohydrates, proteins, glycosides, alkaloids, flavanoids). Providing quality fish feed became a prime aim of every aquaculturist. Though fish feed devours around 50% of the production cost, yet it plays the pivotal role in the production and yield outcome.